Linguistic and Stylistic Polyphony of Occasional Journalism - Wojtak, Maria (Following Rhetoric, Stylistics and Journalism. A Volume Dedicated to Professor Barbara Bogołębska, 2019)
The article has been conceived as an attempt to characterize a particular press publication in the shape of a genre collection. It is an extra to „Tygodnik Powszechny” (No. 29, 2018) under the title “Festiwal Stolica Języka Polskiego” (“Festival the Capital of the Polish Language)”. The publication reproduces a form of press magazine, since apart from the festival program, it includes: an editorial, interviews, reviews, commentaries and silhouettes of selected participants of the festival. Therefore, we deal with a co-occurrence of particular utterances at a specific place and time, typical for a collection. The function of notification about a cultural event (the festival) and the function of promoting the event can be ascribed to the whole issue. The author analyzes the abovementioned publication in the discursive perspective, and so she draws attention to specified communication practices, typical of contemporary press that create a complicated network of strategies, goals and forms of communication, contributing to the shape of contemporary journalism. The analytic purpose of the article is to present a communication polymorphism of a particular set of press utterances that interpret a specified reality and aim at convincing the readers to this interpretation. Particular utterances are treated as voices, i.e. communicatively (pragmatically) and formally shaped types of language activities.